ARTISTIC IMAGE PROBLEM IN AHMAD A'ZAM'S STORIES AND NOVELS - Sidikova Shahnoza Kamoliddinovna (Journals Park Publishing, 2024)
In the articleThe image system of Ahmad Azam's stories is analyzed. The images characteristic of the writer's stories and novellas, their poetic relationship with the artistic plot is studied. In the story, the nature of the human image, its artistic connection with the events of the plot is discussed in detail.
Keywords: story, novella, artistic image, plot, psychological image, human body, artistic detail, motive, composition.